2022
DOI: 10.1038/s41598-022-06594-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between height loss and cardiovascular disease in the Korean elderly

Abstract: Shorter people are at risk for cardiovascular disease (CVD), but data remain limited. This study sought to determine whether height loss is associated with an increased incidence of CVD. From the Korean National Health Insurance Service—Senior database (2002–2015), data of 134,952 individuals with available information on height loss was obtained. Height loss as percentages was measured 3–5 years from the baseline height. To assess hazard ratios for CVD incidence, multivariable Cox proportional hazard regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Our findings were in agreement with Dembowska et al (2022) who suggested that the prevalence of coronary artery disease co-existing with periodontal disease increases as the age advances. This study finding was also consistent with the findings of Nelson et al and Choi et al where the authors stated that there existed a well-established association between a short stature height and increased risk of coronary artery disease and this effect largely remained constant even after adjustment of potential confounders such as smoking status, blood pressure, hypertension and obesity (Choi et al, 2022;Nelson et al, 2015). Pires et al (2013) stated that there is two-fold increased risk of developing coronary artery disease in chronic periodontitis subjects with BMI ≥25 kg/m 2 .…”
Section: Discussionsupporting
confidence: 92%
“…Our findings were in agreement with Dembowska et al (2022) who suggested that the prevalence of coronary artery disease co-existing with periodontal disease increases as the age advances. This study finding was also consistent with the findings of Nelson et al and Choi et al where the authors stated that there existed a well-established association between a short stature height and increased risk of coronary artery disease and this effect largely remained constant even after adjustment of potential confounders such as smoking status, blood pressure, hypertension and obesity (Choi et al, 2022;Nelson et al, 2015). Pires et al (2013) stated that there is two-fold increased risk of developing coronary artery disease in chronic periodontitis subjects with BMI ≥25 kg/m 2 .…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we investigated the relationship between height loss and cardiovascular mortality as a secondary outcome, but we could not find an association between height loss and cardiovascular mortality in men. A recent observational study conducted in South Korea revealed that people with a height loss of greater than 2% had a greater risk of cardiovascular diseases 13 , although subgroup analysis showed significant differences only in the risk of ischemic stroke, but not in myocardial infarction. The limited number of cardiovascular deaths (only 279 in total, 172 in men) in our cohort could be one of the reasons why we found no significant association between height loss and cardiovascular risk in men.…”
Section: Discussionmentioning
confidence: 97%
“…Although osteoporosis is thought to be one of the main factors associated with height loss, especially in the elderly, the resultant height loss affects the normal functioning of the cardiopulmonary and gastrointestinal systems 4 , 5 , which might cause malnutrition and decrease in skeletal muscle mass (sarcopenia) 6 . Several previous studies involving observation for several to a dozen years have reported that marked height loss in the long term is associated with mortality 7 11 , fractures 8 , 12 , and cardiovascular diseases 9 11 , 13 in the elderly. In these previous studies, relationships between height loss and mortality risk were reported separately in men 11 and women 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%